Analisis Faktor Sosial Demografi terhadap Tenaga Kerja Provinsi Gorontalo - Banini, Bhetriana R.; Saleh, Sri Endang; Payu, Boby Rantow (Economic Reviews Journal, 2024)
This research aims to analyze (i) the influence of gender on workers' income (ii) the influence of marital status on the income of formal and informal sector workers (iii) the influence of education level on the income of formal and informal sector workers (iv) the influence of area of residence. On the income of formal and informal sector workers in Gorontalo Province. The data used in this research is secondary data sourced from the Central Statistics Agency obtained from the National Labor Force Survey (SAKERNAS). This research uses logistic regression analysis (multinomial) The results of this research show that socio-demographic factors with indicators of gender, marital status, education level and area of residence have a positive and significant influence on the income of formal and informal sector workers, meaning that every 1 percent increase in socio-demographic factors can increase labor income in Gorontalo Province.